2004
DOI: 10.1590/s0100-879x2004000300009
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-5 mediates peritoneal eosinophilia induced by the F1 cell wall fraction of Histoplasma capsulatum

Abstract: An alkali-insoluble fraction 1 (F1), which contains mainly ß-glucan isolated from the cell wall of Histoplasma capsulatum, induces eosinophil recruitment into the peritoneal cavity of mice. The present study was carried out to determine the participation of interleukin-5 (IL-5) in this process. Inbred C57BL/6 male mice weighing 15-20 g were treated ip with 100 µg of anti-IL-5 monoclonal antibody (TRFK-5, N = 7) or an isotype-matched antibody (N = 7), followed by 300 µg F1 in 1 ml PBS ip 24 h later. Controls (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Total BALF and peritoneal cavity leukocyte counts were immediately performed in a Neubauer chamber. Differential counts were performed using Rosenfeld-stained cytospin preparations [11].…”
Section: Leukocyte Influx Into the Bronchoalveolar Space And Peritonementioning
confidence: 99%
See 2 more Smart Citations
“…Total BALF and peritoneal cavity leukocyte counts were immediately performed in a Neubauer chamber. Differential counts were performed using Rosenfeld-stained cytospin preparations [11].…”
Section: Leukocyte Influx Into the Bronchoalveolar Space And Peritonementioning
confidence: 99%
“…Total cell counts were performed using diluting solution in a Neubauer chamber. Differential counts were obtained using Rosenfeld-stained smears [11].…”
Section: Bone Marrow and Blood Cell Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such leukotrienes are inflammatory mediators and have been shown to recruit leukocytes, such as neutrophils and eosinophils, in various animal and human models [13][14][15]32,33]. In a previous study, we demonstrated that MK 886 inhibited recruitment of neutrophils and eosinophils to the peritoneal cavity after administration of the alkali-insoluble fraction 1 from the cell wall of Histoplasma capsulatum, a dimorphic pathogenic fungus [34]. In the present study, treatment with MK 886 resulted in dose-dependent inhibition of neutrophil and eosinophil recruitment, although no effect on mononuclear cell recruitment was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte recruitment to the site of inflammation is a fundamental event in the inflammatory process. Acute peritonitis promoted by ␤-glucan of cell walls from Histoplasma capsulatum greatly induces leukocyte recruitment, including NE, to the peritoneal cavity (Medeiros et al, 1999;Sá-Nunes et al, 2004). This model is easy to reproduce and is widely used in our laboratory to screen plants extracts, their fractions as well as secondary metabolites regarding their anti-inflammatory activity (Rogerio et al, 2006).…”
Section: Introductionmentioning
confidence: 99%